Economic Consequences of the Ukraine-Russia War: Impacts on Global Trade and Financial Stability - Eshaq Mahir (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
The Ukraine-Russia war, which erupted in 2022, has generated profound disruptions in global trade and financial stability. This paper explores the economic consequences of the conflict, focusing on the far-reaching impacts on supply chains, international trade relations, and financial markets. The war has led to sharp increases in energy and food prices, exacerbated inflationary pressures worldwide, and prompted significant volatility in global financial markets. Moreover, the imposition of sanctions on Russia has intensified economic fragmentation, with long-term consequences for global trade and investment. By analyzing key economic sectors—energy, agriculture, and finance—this paper provides a comprehensive assessment of the direct and indirect effects of the conflict on the global economy and highlights the potential long-term risks for economic stability.